Sons do clássico: no 100º aniversário de Maria Augusta Barbosa - Maria Margarida Lopes de Miranda (Documentos, 2012)
This homage to Maria Augusta Barbosa on the occasion of the 100th anniversary of her birth explores the classical style in the broader, though not diffuse, sense of the term with a series of previously unpublished accounts both by and about this unrivalled figure from the world of Portuguese musicology. The authors, all of whom were related to her in some way through their studies, her teaching or simply friendship, affirm her significance through their important contributions to matters that were included in her teaching, such as themes from classical theory, along with music history, analysis and practice, within the relationship between music, the arts and philosophy. This work opens up new possibilities for the academic exploration of the classical in music, with important names such as Gerhard Doderer, Klaus Niemöller, Gil Miranda, Mário Vieira de Carvalho, Salwa Castelo Branco, Vítor Serrão, and others.